GROUP COUNSELING FOR ADOLESCENT - Tina Afiatin (Buletin Psikologi, 1996)
Recently there are some phenomenon about adolescent maladjusment, for instances: juvenile delinguency, student riots, drug abuse, and even killing cases (Republika, December 13, 1993). Maladjusment of adolescent happens when adolescents or teenagers fail to satisfy their needs and thus feel frustrated.